Primary Cutaneous Follicle Center Lymphoma Associated With an Extracutaneous Dissemination: A Cytogenetic Finding of Potential Prognostic Value. Issue 5 (1st November 2015) - Subramaniyam, Shivakumar; Magro, Cynthia M.; Gogineni, Swarna; Tam, Wayne; Mathew, Susan
Abstract: Objectives: Cytogenetic studies on cutaneous lymphomas are rare, and very little is known about their prognostic value. We present a rare case of primary cutaneous follicle center lymphoma (PCFCL) with a complex translocation presenting with cutaneous and extracutaneous dissemination in the lymph node. Methods: Morphologic, immunohistochemical, conventional cytogenetic, and fluorescence in situ hybridization (FISH) studies were performed on this patient. Results: A combination of cytogenetic and FISH analysis identified a complex novel four-way t(2;14;9;3) (p11.2;q32;p13;q27) translocation involving rearrangements of BCL6, immunoglobulin light and heavy chain genes, and an unknown gene on 9p. Conclusions: Our report elaborates the morphologic and immunohistochemical features in combination with cytogenetic and molecular cytogenetic analysis of PCFCL, which provide additional insight into the clinical and biologic behavior of this lesion.